UPAYA MENINGKATKAN KEPUASAN WISATAWAN MELALUI THE ATTRACTION OF TOUR DI TJP SERATOUR - Ridwanudin, Oce; Saputra, Nugraha Adi (THE Journal : Tourism and Hospitality Essentials Journal, 2016)
The attraction of tourists to use the tour affecting travel services until they feel the satisfaction or dissatisfaction as a result of the products and services provided to tourists by a company providing travel services. This research was conducted with the aim to describe the attraction of the tour at the TJP Seratour, tourist satisfaction and the influence of the attraction of the tour to tourist satisfaction. The population in this study is the tourists who use the services of a travel in Seratour TJP 100 respondents. The method used is descriptive and verification with research time of less than one year (cross-sectional method). The sampling technique used is systematic random sampling. The data analysis technique used is the technique of multiple regression analysis. Hasi This study shows that the highest impact on the attraction of the tour is the variable sub lowest access and influence is convenience. Simultaneously te attraction of the tour to have a significant impact on tourist satisfaction, the same thing happens to the partial test, which occurred a significant influence between the attraction of the tour to tourist satisfaction.